The Effect of Infographic Utilisation Assisted by LMS SPADA to Improve Understanding of the Concept of Light Reflection in Basic Physics Course for D3 Pharmacy Students UMMAT in 2023 - Islahudin; Linda Sekar Utami; Hamzah (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This research is entitled The Effect of Infographic Utilisation Assisted by LMS SPADA DIKTI to Improve Understanding of the Concept of Light Reflection in Basic Physics Course for D3 Pharmacy Students of UMMAT in 2023. The purpose of this study was to determine the effect of the use of infographics assisted by LMS SPADA on improving understanding of the concept of light reflection in the Basic Physics Course for D3 Pharmacy students of UMMAT Odd Semester Academic Year 2023/2024.. The research location is D3 Pharmacy Study Programme, FIK, UMMAT Academic Year 2023/2024. The study population was all students of the D3 Pharmacy Study Programme, UMMAT. The sample in this study were 16 D3 Pharmacy students of class 2023 who were taking Basic Physics courses. The research method used is the Pre-experiment method. The research design used was one group pretest-posttest design. Data collection was carried out using test instruments. The instrument used in this research is in the form of a concept understanding test that measures the cognitive domain. The number of questions is 25 multiple choice questions. Based on the results of the study, it can be concluded that there is a significant effect of using infographics assisted by LMS SPADA to improve the understanding of the concept of light reflection material for D3 Pharmacy UMMAT students in the 2023/2024 Academic Year in the Basic Physics course. The N-gain value is 0.612 so that the increase in understanding of the concept of student light reflection in basic physics courses is in the medium category